The second year of a second chance: Long-term psychosocial outcomes of cardiac arrest survivors and their family. (October 2021) - Case, Rosalind; Stub, Dion; Mazzagatti, Emilia; Pryor, Holly; Mion, Marco; Ball, Jocasta; Cartledge, Susie; Keeble, Thomas R.; Bray, Janet E.; Smith, Karen
Abstract: Aim: Cardiac arrest (CA) survival has diverse psychosocial outcomes for both survivors and their close family, with little known regarding long-term adjustment and recovery experiences. We explored the psychological adjustment and experiential perspectives of survivors and families in the second year after out-of-hospital cardiac arrest (OHCA). Methods: A prospective, mixed-methods study of adult OHCA survivors in Victoria, Australia was conducted. Eighteen survivors and 12 family members completed semi-structured interviews 14–19 months post-arrest. Survivors' cognition, anxiety, depression and post-traumatic stress symptoms were measured using a battery of psychological assessments. A thematic content analysis approach was applied to qualitative interview data by two independent investigators, with data coded and categorised into themes and sub-themes. Results: Survivors' cognition, depression, anxiety and post-traumatic stress symptoms were not clinically elevated in the second year post-arrest. Subjective cognitive failures were associated with increased anxiety but not with mental state. Depression was significantly correlated with post-traumatic symptoms. Six primary themes emerged from survivors' recovery stories, focused on: awakening and realisation, barriers to adjustment, psychosocial difficulties, integration, protective factors and unmet needs. Family perspectives revealed four primary themes focused on trauma exposure, survivor adjustment problems, family impact, and areas for service improvement. Conclusion: Survivors and their family members describe complex recovery journeys characterised by a range of psychosocial adjustment challenges, which are not adequately captured by common psychological measures. Post-arrest care systems are perceived by survivors and their families as inadequate due to a lack of accurate information regarding post-arrest sequalae, limited follow-up and inconsistent access to allied health care.